PENGEMBANGAN PRODUK YANG BERPOTENSI SEBAGAI MINUMAN FUNGSIONAL UNTUK PENDERITA PRAHIPERTENSI - Yuni, Sri; Madanijah, Siti; Setiawan, Budi; Marliyati, Sri Anna (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2016)
This study aimed to develop a functional beverage for patients with prehypertension. Raja Bulu banana (Musa paradisiaca L.) and Wilis variety of soy beans (Glycine max L.) are used as ingredients for functional beverages production. This study used a completely randomized design and the treatments were given in three formulas with different proportion of soy milk (mL) and banana (g), namely F1 (1000:250), F2 (1000:350), and F3 (1000:500). The results of Kruskal-Wallis test showed that the average preference of colour, flavor, taste, and viscosity characteristics among the three formulas were not significantly different (p>0.05). The most preferred functional beverage formula was F3, chosen by 88.00% of panelists. One serving size (300 mL) of F3 functional beverage contained 149 kcal energy, 34.68 g carbohydrates, 1.91 g protein, 0.24 g fat, 3.95 g dietary fiber, 26.76 g total sugars, 7.00 mg sodium, 401.20 mg potassium, 13.84 mg calcium and 42.16 mg magnesium. Therefore, the product is potential to be a functional beverage alternatives, especially for prehypertension patients.